2004
DOI: 10.1016/j.rapm.2003.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative cognitive function as an outcome of regional anesthesia and analgesia

Abstract: The use of intraoperative neuraxial anesthesia does not appear to decrease the incidence of postoperative cognitive dysfunction when compared with general anesthesia. There are methodologic and study-design issues present in many studies, and further elucidation of the pathophysiology of postoperative cognitive dysfunction may provide a direction for future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 95 publications
(132 reference statements)
1
66
2
1
Order By: Relevance
“…A surprising, but consistent, fi nding which argues against general anesthetics as a cause of POCD is the fact that the incidence of POCD after regional anesthesia and after general anesthesia is similar [24,25]. In 19 trials patients were randomized to general or regional techniques.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…A surprising, but consistent, fi nding which argues against general anesthetics as a cause of POCD is the fact that the incidence of POCD after regional anesthesia and after general anesthesia is similar [24,25]. In 19 trials patients were randomized to general or regional techniques.…”
Section: Pathophysiologymentioning
confidence: 99%
“…In 19 trials patients were randomized to general or regional techniques. In only 1 of these studies a small difference in the incidence of POCD was detected, in favor of patients allocated to regional anesthesia [25]. A limitation of these studies is the fact that patients operated under regional anesthesia frequently received sedatives, usually low-dose benzodiazepines or propofol.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Postoperative delirium was reported in a similar frequency in previous studies [28][29][30]. However, in contrast to previous work, we did not use a specific delirium scale for diagnosis.…”
Section: Discussionmentioning
confidence: 67%
“…Neither had advantages for the recovery of cognitive functions in geriatric patients during the first three days after the surgery (Dahn et al, 1999). Randomized clinical studies did not show a prevalence of any special kind of anesthesia in POCD prevention (Wu, et al, 2004). Moreover, in 2009, Avidan et al (Avidan et al, 2009), in his retrospective cohort study including 575 patients, did not find a long-term cognitive impairment due to surgery and illness.…”
Section: Pocd and Anesthesiamentioning
confidence: 96%
“…The high incidence of cognitive dysfunction in orthopedic patients can result (apart from the above mentioned risk factors) from long bone fractures, prolonged immobilization, and partially from perioperative stress (Wu, et al, 2004) or a surgery technique. Colonna et al concluded that the incidence of cerebral embolization after lower extremities arthroplasties was up to 40 -60% (Colonna et al, 2002).…”
Section: Etiology Of Pocdmentioning
confidence: 99%